Characteristics of Sexual and Gender Minority Caregivers of People With Dementia. (December 2021) - Anderson, Joel G.; Flatt, Jason D.; Jabson Tree, Jennifer M.; Gross, Alden L.; Rose, Karen M.
Objectives: Given what little is known about the experiences of sexual and gender minority (SGM) caregivers of people with Alzheimer's disease and related dementias (ADRD), the aim of the current study was to describe psychosocial measures among these caregivers.Methods: We used an online survey and social media recruitment strategies.Results: Of 286 caregivers, the majority were gay men. Most respondents were white, with a third identifying as Latino American. The plurality of caregivers identified as a spouse/partner and were providing care for someone who identified as a sexual minority; one-fifth cared for someone transgender. Sexual orientation, perceived stress, caregiver stigma, and microaggressions were psychosocial factors associated with family quality of life and depressive symptoms in the caregivers.Discussion: This study is the first to provide a focused description of the characteristics and psychosocial needs of SGM caregivers of someone with ADRD, supporting development of targeted interventions for this population.